Exploring the Stability of Novel Wide Bandgap Perovskites by a Robot Based High Throughput Approach. Issue 6 (4th October 2017) - Chen, Shi; Hou, Yi; Chen, Haiwei; Tang, Xiaofeng; Langner, Stefan; Li, Ning; Stubhan, Tobias; Levchuk, Ievgen; Gu, Ening; Osvet, Andres; Brabec, Christoph J.
Abstract: Currently, lead‐based perovskites with mixed multiple cations and hybrid halides are attracting intense research interests due to their promising stability and high efficiency. A tremendous amount of 3D and 2D perovskite compositions and configurations are causing a strong demand for high throughput synthesis and characterization. Furthermore, wide bandgap (≈1.75 eV) perovskites as promising top‐cell materials for perovskite–silicon tandem configurations require the screening of different compositions to overcome photoinduced halide segregation and still yielding a high open‐circuit voltage ( V oc ). Herein, a home‐made high throughput robot setup is introduced performing automatic perovskite synthesis and characterization. Subsequently, four kinds of compositions (i.e., cation mixtures of Cs–methylammonium (MA), Cs– formamidinium (FA), MA–FA, and FA–MA) with an optical bandgap of ≈1.75 eV are identified as promising device candidates. For Cs–MA and Cs–FA films it is found that the Br–I phase segregation indeed can be overcome. Moreover, Cs–MA, MA–FA, and Cs–FA based devices exhibit an average V oc of 1.17, 1.17, 1.12 V, and their maximum values approached 1.18, 1.19, 1.14 V, respectively, which are among the highest V oc (≈1.2 V) values for ≈40% Br perovskite. These findings highlight that the high throughput approach can effectively and efficiently accelerate the invention of novel perovskites for advanced applications. Abstract : A home‐made high throughput robot system is constructed and able to perform automatic perovskite synthesis and characterization. 95 perovskite compositions are tested to identify the most promising combinations for wide bandgap perovskites as required for tandem applications, and this highlights the relevance and the benefit of high throughput screening novel perovskites for advanced devices solutions.